Determination of Human Serum Protein by Molecularly Imprinted Polymer Derivatized. Issue 1 (9th October 2014) - Dong, Yanjie; Huang, Xuming; Wang, Fang; Wang, Junwei; Xia, Hongyu; Wang, Zhongling
Abstract Determination of human serum protein by molecularly imprinted polymer (MIP) derivatized inner wall of capillary coupling of capillary‐electrophoresis was successfully developed. The vinyl groups were introduced onto the silica by immobilization of ‐methacryloxypropyltrimethoxysilane. Then the MIP coating was copolymerized and anchored onto the surface of the silica. The other preparation conditions, such as monomer concentration, temperature, and time of polymerization, were systematically studied. The obtained MIP‐derivatized capillary was applied to capillary electrophoresis, which was used for the separation and determination of human serum protein. The optimization of the experimental conditions was determined by evaluating various controlling factors: running buffer pH = 9.6, 0.1 mol L‐1 boric acid‐sodium borate, separation voltage 30 kV, temperature 25 °C, detected wavelength 192 nm.